Smart Tourism Triggers Tourist Minds-Do you have the mind to mind it? (Vallis Aurea, 2023)
This paper explores the impact of smart tourism on rural communities, particularly through economic diversification enabled by digital transformation. Smart tourism, driven by rapid technological advancements, is reshaping the tourism industry, especially in the wake of the COVID-19 pandemic, which severely disrupted the sector. The industry now requires strategic innovations in destinations, services, and business models.The core research question is: What is the importance of smart tourism, and how has it influenced tourist behavior? The study focuses on emerging countries, with a special emphasis on Uzbekistan, using a conceptual approach to analyze tourism business challenges and opportunities.A key aspect of the research is examining the role of trust and its relationship to smart tourism dissemination in digital marketing, viewed through the Theory of Mind (ToM). ToM helps enhance the perception of smart destinations, influencing tourist behavior positively.Findings highlight the importance of innovation in tourism, noting both its benefits and barriers in developing contexts. Digital transformation is identified as a vital tool for promoting sustainable tourism, improving the quality of life for both tourists and local communities. Ultimately, smart tourism enhances the overall travel experience and creates added value for all stakeholders.